Measuring the effectiveness of synchronous and asynchronous electronic learning on academic performance - Mohammad Zare; Mohammadreza Nili; Esmail Zarizavaraki; Mohammad Asgari (مجله ایرانی آموزش در علوم پزشکی, 2022)
Introduction: The purpose of e-learning is to create favorable learning cognitions in the instructional-learning process. One of the success criteria in these courses is awareness of this learning method and its proper use. This study endeavored to investigate the effectiveness of synchronous and asynchronous e-learning on students' academic performance. Methods: This was applied study with a pre-test-post-test research design included control and experimental groups. The research population included all undergraduate nursing students of Hamedan University of Medical Sciences in the second semester of the academic years 2021-2022 (about 260 individuals). From this population, 30 individuals were purposefully selected and randomly assigned to control and experimental groups (15 individuals in each group). Initially, the academic performance pre-test was conducted for both groups. Then, the control group was taught the content of the psychology course in the form of asynchronous e-learning, and the experimental group was taught the same content in the form of synchronous e-learning. Afterwards, the academic performance post-test was administered for both groups. The instrument used included a 20-question objective test of pre-test and post-test academic performance from the psychology course. The content validity of this tool was verified through the confirmation of psychological experts. The reliability of the tool was calculated through Cronbach's alpha for pre-test 81% and post-test 79%. To analyze the data, covariance test was used. Results: The result showed that there is a significant difference between the scores of the academic performance of the psychology course in the post-test of the two groups trained by the synchronous method (p< .001): and the use of e-learning at the experimental group promoted the academic performance in the psychology course. Conclusion: Based on the purpose of the electronic teaching-learning process, the use of synchronous learning improves the academic performance of students. Accordingly, planning and using this method is recommended.